The medicinal and wild food plants of Batman City and Kozluk District (Batman-Turkey) - (:unkn) unknown (University of Zagreb, 2019)
This paper reports an ethnobotanical investigation carried out in 2012 to record medicinal and wild food plants of Batman City and Kozluk District. Totally, forty-one plants are recorded as used as traditional folk medicine for the region, and twenty of these are also used as a source of wild food. The most commonly used plants in the region as medicinal remedies were Malva nicaeensis, Pistacia khinjuk, Plantago major subsp. intermedia and Teucrium polium. Plants are mostly used for the treatment of gastrointestinal system diseases, respiratory system diseases and diabetes. The species most commonly used for food are: Gundelia tournefortii, Pistacia khinjuk and Rhus coriaria. This ethnobotanical study conducted in both districts will enable the traditional use of wild plants both as food sources and herbal remedies to be passed on to future generations. © 2019, University of Zagreb. All rights reserved.
Keywords: Batman; Ethnobotany; Traditional medicine; Turkey; Wild food plants